Assistance in the selection of village officials in Tirtonirmolo Village, Kapanewon Kasihan, Bantul Regency - Septi Nur Wijayanti; Nanik Prasetyoningsih; Kelik Iswandi; Ruby Nur Adilla (Community Empowerment, 2022)
The existence of a vacancy in the village head office may affect the village's service process. With three vacant village civil service positions, the Government of Tirtonirmolo Village, Kapanewon Kasihan, Bantul Regency, DI Yogyakarta had a vacancy problem. These issues can be resolved by using a selection exam system to pick village authorities. This program aims to provide assistance in the selection process for village officials. Coordination with the village committee, identification and preparation of exam questions, and implementation of the selection of candidates for village authorities are all steps of this service. As a result of this service, a selection system that complies with regional regulations has been developed. The results of the selection are also made transparent by announcing it in front of the selection exam participants and the village selection committee.